Strategies and instruments for active mobility: comparison of international experiences - D'Amico, Annunziata (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of continuously updating emerging topics concerning relationships between urban planning, mobility and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of four parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Urban strategies, programmes and tools section presents the different strategies and tools for active mobility implemented internationally. The contribution aims to address the issue of active mobility in the context of sustainable urban planning on a global scale. In this direction, this review provides an overview of strategies and tools that promote active mobility options in urban areas and identify best practices from cities around the world. In recent sustainable urban mobility policies, at all levels of governance, the focus has been on active mobility identified as one of the key components for the transition to a neutral climate and an inclusive urban future, more resilient and safer.